Faktor-faktor yang mempengaruhi penyerapan anggaran pada satuan kerja pendidikan madrasah aliyah negeri di Provinsi Jambi - Mubarik; Yulmardi; Erni Achmad (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2022)
The aims of this study are 1) to find out and analyze the description of planning documents, administrative records, human resource competencies, procurement documents, money supply and budget absorption in the Madrasah Aliyah Negeri Education Work Unit in Jambi Province. 2) To analyze the effect of planning documents, administrative records, human resource competence, procurement documents and money supply on budget absorption in the State Madrasah Aliyah Education Unit in Jambi Province.This type of research is descriptive quantitative. The type of data used for processing this research data is primary data with the analytical tool used is multiple linear regression. Based on the results of multiple linear regression, it shows that planning documents, administrative records, human resource competencies, and money supply have a significant effect on budget absorption in the State Madrasah Aliyah Education Work Unit in Jambi Province. Meanwhile, procurement documents have no significant effect on budget absorption in the State Madrasah Aliyah Education Unit in Jambi Province.